2019
DOI: 10.1016/j.ijdevneu.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal vaginal inflammation increases anxiety and alters HPA axis signalling in adult male mice

Abstract: Background Maternal infection during pregnancy is known to adversely affect foetal development, but previous studies have rarely investigated the impact of gynaecological diseases during pregnancy on offspring during adulthood. Vaginitis is one of the most prevalent gynaecological diseases during pregnancy. Methods The effect of maternal vaginal inflammation on offspring was simulated by inducing maternal vaginal infection. We performed a transvaginal injection of lipopolysaccharide (LPS) in pregnant mice to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…Similar observations have been reported for the progeny of mouse dams injected with LPS at GD9 when challenged in adulthood [ 103 ]. Also, the offspring prenatally exposed to intrauterine inflammation [ 104 ] and vaginitis [ 105 ], which are both induced by LPS treatment, manifested anxiety-related behaviours. Additionally, in our study, the LPS-treated adult male rats did not display any changes in social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been reported for the progeny of mouse dams injected with LPS at GD9 when challenged in adulthood [ 103 ]. Also, the offspring prenatally exposed to intrauterine inflammation [ 104 ] and vaginitis [ 105 ], which are both induced by LPS treatment, manifested anxiety-related behaviours. Additionally, in our study, the LPS-treated adult male rats did not display any changes in social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our data, rats prenatally treated with LPS displayed more anxiety-like behaviours and enhanced stress responses [ 71 ]. Also, the offspring exposed to intrauterine inflammation [ 72 ] and vaginitis [ 73 ] before birth, which are both induced by LPS injection, manifested anxiety-related behaviours. Nevertheless, different species or strains, as well as diverse test conditions, exert crucial effects on the outcome of animal examinations of anxiety [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“… Hernandez et al (2020) demonstrated that there are no significant differences between the sexes in age-related cognitive impairment (including spatial and working memory) in rats. Wang et al (2019) showed that prenatal exposure to inflammation leads to increased anxiety-related behavior in adult male offspring when compared with adult female offspring. Fernández de Cossío et al (2017) also reported a male-specific effect for intrauterine LPS exposure on synaptic pruning in the hippocampus of adult offspring, while the observed LPS-induced anxiety-related behavior deficits did not differ between the sexes.…”
Section: Discussionmentioning
confidence: 99%